KINERJA KEUANGAN DAERAH DAN DETEKSI ILUSI FISKAL PADA PEMERINTAH DAERAH KABUPATEN/KOTA PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Riztika Dyahningtyas; Sri Suharsih; Sri Rahayu Budi Astuti (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This research aims to : (1) Analyzing the financial performance of districts/cities in the Daerah Istimewa Yogyakarta Province; (2) Analyzing the phenomena of fiscal illusions that occur in the finance of districts / cities in DIY Province. This research is based on secondary data, namely the Local Goverment Budget and Local Gross Domestic Product data sourced from the Ministry of Finance DJPK and BPS. The analytical tool used is financial independence ratio analysis, fiscal decentralization degree and panel data regression analysis. Based on the results of the analysis, it is known that the average independence ratio of the Regency / City of DIY Province is 30,38% and has a pattern of consultative relations with the central government. In the degree of fiscal decentralization, it is known that the Regency / City average is 17,35%. This means that the capacity of regional governments to manage regional finance is still lacking. In addition, there is a phenomenon of fiscal illusion in the financial performance of the Regency / City Regional Government of the DIY Province.